Compounds of Citrus medica and Zingiber officinale for COVID-19 inhibition: in silico evidence for cues from Ayurveda - M. Haridas; Vijith Sasidhar; Prajeesh Nath; J. Abhithaj; A. Sabu; P. Rammanohar (SpringerOpen, 2021)
Abstract Background The nasal carriage of SARS-CoV-2 has been reported as the key factor transmitting COVID-19. Interventions that can reduce viral shedding from the nasopharynx could potentially mitigate the severity of the disease and its contagiousness. Herbal formulation of Citrus medica and Zingiber officinale is recommended in an Ayurvedic text as a nasal rinse in the management of contagious fevers. These herbs are also indicated in the management of respiratory illnesses and have been attributed with activity against pathogenic organisms in other texts. Molecular docking studies of the phytocompounds of C. medica and Z. officinale were done to find out whether these compounds could inhibit the receptor binding of SARS-CoV-2 spike protein (S protein) as well as the angiotensin-converting enzyme 2 (ACE-2), as evidenced from their docking into binding/active sites. Results The proteins of SARS-CoV-2, essential for its entry into human cells and highly expressed in the goblet and ciliated cells of nasal epithelium, play a significant role in contagiousness of the virus. Docking studies indicated that the specific compounds present in C. medica and Z. officinale have significant affinity in silico to spike protein of virus and ACE-2 receptor in the host. Conclusion In silico studies suggest that the phytochemical compounds in C. medica and Z. officinale may have good potential in reducing viral load and shedding of SARS-CoV-2 in the nasal passages. Further studies are recommended to test its efficacy in humans for mitigating the transmission of COVID-19.